Implementing Competency Framework at Bharat Dynamics Ltd. (BDL). (December 2015) - Raju, N.K.; Sarkar, Shulagna
Competency based practices have been in existence for quite some time; yet, not many public sector organizations in India have been formally practicing it. In 2010, the HR guidelines issued by the Department of Public Enterprises (DPE) highlighted the need for competency based HR practices as one of the four pillars of the HR function. Bharat Dynamics Limited (BDL) is a Central Public Sector Enterprise (CPSE) and has received the status of Mini Ratna (Category-I) company of India. The article discusses the implementation of the competency framework at BDL and links it to performance management system. The linkage of the competency framework to compensation and training and development at BDL has also been highlighted. The article provides useful guidelines for other companies, which are planning to initiate competency based HR practices.